'Just another person in the room': young people's views on their participation in Child in Care Reviews. (December 2018) - Diaz, Clive; Pert, Hayley; Thomas, Nigel
This article discusses a key meeting for children in care – the Child in Care Review – and examines the extent to which children and young people are able to participate and exert a level of control over their lives. The research, conducted in England, formed part of a wider exploration of the views and experiences of all those involved in such reviews, namely Independent Reviewing Officers (IROs), social workers, senior managers and – the focus of this article – the young people concerned. Most of the children interviewed said that they found their reviews frustrating and stressful, often attributing this to poor relationships with social workers and scepticism about the value of the review process. However, they recognised the workload pressures facing social workers and the bureaucratic constraints affecting the service they received. The article argues for the continuing importance of the IRO role, given the consistency it provides for children in care. It also shows that while it provides an opportunity for children's participation in discussions about their future, the Child in Care Review is underperforming. The developing practice of children chairing their own reviews offers one way forward and the article calls for this to be developed and for other creative methods to be introduced to enable young people to play a meaningful part in meetings that affect them.